2012
DOI: 10.1016/j.kjms.2012.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different implant materials on the primary stability of orthodontic mini‐implants

Abstract: This study evaluates the influence of different implant materials on the primary stability of orthodontic mini-implants by measuring the resonance frequency. Twenty-five orthodontic mini-implants with a diameter of 2 mm were used. The first group contained stainless steel mini-implants with two different lengths (10 and 12 mm). The second group included titanium alloy mini-implants with two different lengths (10 and 12 mm) and stainless steel mini-implants 10 mm in length. The mini-implants were inserted into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 23 publications
1
24
0
2
Order By: Relevance
“…Degidi et al 18 observed a slight correlation, whereas Park et al 19 reported a significant linear correlation. The observed correlation between ID and RFA was also investigated in in vitro studies by Kang et al 20 for dental implants and by Pan et al 21 for miniimplants. The IT did not correlate with ID.…”
Section: Discussionmentioning
confidence: 81%
“…Degidi et al 18 observed a slight correlation, whereas Park et al 19 reported a significant linear correlation. The observed correlation between ID and RFA was also investigated in in vitro studies by Kang et al 20 for dental implants and by Pan et al 21 for miniimplants. The IT did not correlate with ID.…”
Section: Discussionmentioning
confidence: 81%
“…There are some studies assessing the influence of different materials [6] or surface treatment [7] to enhance cellular reaction and micro retention. Other studies focus on macroscopic design elements such as thread and taper design [8].…”
Section: Introductionmentioning
confidence: 99%
“…Accurate measurement orthodontic MSI stability is a continuing challenge. This study compared the effects of different materials on the primary stability of MSIs by using a relatively new RF analyzer, the Implomates device, which was used in a previous study of artificial bones (8). To our knowledge, this is the first clinical study to use the Implomates to evaluate change in MSI stability during the wound healing.…”
Section: Discussionmentioning
confidence: 99%